Perforator-Based Propeller Flap with Additional Venous Pedicle for Lower Limb Reconstruction - Mishra, Jiten Kumar; Sahu, Shamendra Anand; Bodhey, Narendra Kuber; Sindhuja, Abi; V., Abhijith (Indian Journal of Plastic Surgery, 2023)
Propeller flaps are effective reconstructive tools for small-to-medium sized defects of the lower limb and a reasonable alternative to free flaps. A major vessel of the lower limb remains undisturbed while raising the flap and the flap donor and recipient areas are addressed in the same operative field. Perforator-based propeller flaps are based on single perforator arising from a major vessel and during rotation of the larger paddle there is a possibility of kink in the venous component leading to congestion of flap. In our modification, one superficial vein of the lower limb namely the great saphenous or short saphenous vein was included in the flap territory to enhance the retrograde or antegrade venous drainage of the flap. We observed, no flap congestion or necrosis in the postoperative period. Also, the patency of the incorporated vein was confirmed using handheld and color Doppler.
Keywords: propeller flap; modified propeller flap; perforator propeller flap; lower extremity reconstruction